2014
DOI: 10.1542/hpeds.2013-0031
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain Management in Children, Parental English Proficiency, and Access to Interpretation

Abstract: BACKGROUND AND OBJECTIVE Patients with limited English proficiency (LEP) are at risk for undertreated pain. The goal of this study was to examine the association between parental language proficiency, interpreted care, and postsurgical pediatric pain management. METHODS This was a retrospective matched cohort study among children <18 years of age. Children of LEP and English-proficient (EP) parents were matched according to age group, surgical procedure, and admission date. Mean number of daily pain assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 34 publications
2
46
2
1
Order By: Relevance
“…Despite regulatory requirements that health care settings provide access to language services at no cost, 30,31 recent studies of pediatricians demonstrate that many report routinely using non-professional interpreters such as family members. 9, 32-35 Evidence-based standardization of care transitions from acute care to outpatient rehabilitation for moderate to severely injured children with TBI will be important to address service inequalities. Understanding cultural needs and potential barriers to service access are also important next steps.…”
Section: Discussionmentioning
confidence: 99%
“…Despite regulatory requirements that health care settings provide access to language services at no cost, 30,31 recent studies of pediatricians demonstrate that many report routinely using non-professional interpreters such as family members. 9, 32-35 Evidence-based standardization of care transitions from acute care to outpatient rehabilitation for moderate to severely injured children with TBI will be important to address service inequalities. Understanding cultural needs and potential barriers to service access are also important next steps.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, children of Hispanic ethnicity had greater odds of deterioration in HRQOL after surgery admission, however this was not statistically significant. Hispanic ethnicity has been shown to correlate with poorer postsurgical pain treatment in children 14 , which may have contributed to poorer recovery of HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study showed that black children in the ED were less likely than white children with similar levels of abdominal pain to receive analgesic medication [31]. In another study, children whose parents had limited English language proficiency had their pain assessed less frequently during postsurgery care and experienced greater pain levels before receiving analgesic medication [32]. And a growing body of research demonstrates that physicians and other health care professionals exhibit implicit (i.e., unconscious) biases based on race [33,34].…”
Section: Practice Standards and The Ethical Case For Trauma-informed mentioning
confidence: 99%